2012
DOI: 10.1126/science.1227548
|View full text |Cite
|
Sign up to set email alerts
|

Drought in Africa Caused Delayed Arrival of European Songbirds

Abstract: Despite an overall advancement in breeding area arrival, one of the latest spring arrivals in northwest Europe since 1950 of several trans-Saharan songbird species occurred in 2011. Year-round tracking of red-backed shrikes and thrush nightingales revealed that the cause of the delay was a prolongation of stopover time during spring migration at the Horn of Africa, which was affected by extreme drought. Our results help to establish a direct link at the individual level between changes in local climate during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
172
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(187 citation statements)
references
References 9 publications
4
172
2
Order By: Relevance
“…Differences in fundamental niches alone are insufficient to explain, for instance, the striking differences, in some cases, between the wintering grounds and migration routes of closely related species, such as found in Ficedula flycatchers [8,9] and Luscinia nightingales [10,11]. Such patterns could be caused by different population histories (potentially explaining why birds circumvent the Mediterranean via the eastern or the western flyway) or competitive exclusion.…”
mentioning
confidence: 97%
“…Differences in fundamental niches alone are insufficient to explain, for instance, the striking differences, in some cases, between the wintering grounds and migration routes of closely related species, such as found in Ficedula flycatchers [8,9] and Luscinia nightingales [10,11]. Such patterns could be caused by different population histories (potentially explaining why birds circumvent the Mediterranean via the eastern or the western flyway) or competitive exclusion.…”
mentioning
confidence: 97%
“…Impacts include loss of life, crop failures and food shortages, health issues, and mass migration [1] and the consequences on society and the environment are far reaching. For example, Tøttrup et al [2] have reported the impact of drought at the Horn of Africa on the phenology of the songbirds' migrations to Europe. The environmental effects of droughts in Amazonia, a very humid region, have included forest fires, reductions of biomass, and forest mortality [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is an urgent and dire need to progress on various fronts of drought mitigation such as early warning and forecasting, building the resilience of the societies, shortterm relief efforts, long-term planning and capacity building (e.g. Calow et al, 2010;Clarke et al, 2012;Dondero, 1985;Falkenmark and Rockström, 2008;GFDRR, 2011;IFAD, 2010IFAD, , 2011aLogar and van den Bergh, 2013;Mishra and Singh, 2010;Msangi, 2004;Sehmi and Kundzewicz, 1997;Tadesse et al, 2008;Tøttrup et al, 2012;UNISDR, 2004UNISDR, , 2010Vicento-Serrano et al, 2012;Vogel et al, 2010;World Bank and GFDRR, 2010).…”
mentioning
confidence: 99%